Progress and Challenges for Implementation of the Common Market for Eastern and Southern Africa Policy on Biotechnology and Biosafety - Waithaka, Michael; Belay, Getachew; Kyotalimye, Miriam; Karembu, Margaret (Frontiers in Bioengineering and Biotechnology, 2015)
In 2001, the Meeting of the COMESA Ministers of Agriculture raised concerns that proliferation of genetically modified organisms (GMOs) could impact significantly on trade and food security in the region. This triggered studies on a regional approach to biotechnology and biosafety policy in Eastern and Southern Africa. The studies and stakeholder consultations revealed that farm incomes would increase if they switched from conventional varieties of cotton and maize to genetically modified (GM) counterparts. Commercial risks associated with exports to GM sensitive destinations, e.g., EU were negligible. Intra-regional trade would be affected since exports of GM sensitive commodities, such as maize, cotton, and soya bean, mainly go to other African countries. These findings justified the need to consider a regional approach to biosafety and led to the drafting of a regional policy in 2009. The draft policies were discussed in regional and national workshops between 2010 and 2012 for wider ownership. The workshops involved key stakeholders including ministries of agriculture, trade, environment, national biosafety focal points, biosafety competent authorities, academia, seed traders, millers, the media, food relief agencies, the industry, civil society, competent authorities, and political opinion leaders. The COMESA Council of Ministers in February 2014 adopted the COMESA policy on biotechnology and biosafety that takes into account the sovereign right of each member state. Key provisions of the policy include recognition of the benefits and risks associated with GMOs; establishment of a regional-level biosafety risk-assessment system; national-level final decision, and capacity building assistance to member states. The policies are the first regional effort in Africa to develop a coordinated mechanism for handling biosafety issues related to GMO use. A regional approach to biotechnology and biosafety is expected to foster inter-country cooperation through the sharing of knowledge, expertise, experiences, and resources.